Effects of Cavities on Lining Structure behind Cold Zone Tunnels Based on Coupled Thermal Analysis - Xian Xiao; Jianwei Nie (Geofluids)
There is a significant difference between ambient temperature and internal temperature of surrounding rock in the cold season. Based on the Dulongjiang (DLJ) Tunnel, this paper studies the influence of frost heave force on lining structure and establishes a thermos-dynamical coupling model using the field. The results show that the environmental temperature and the cavity behind the lining greatly influence the safety of the tunnel structure. The internal force of the tunnel lining increases with the decrease of the environmental temperature and stress. The existence of a water-bearing cavity causes the deformation of the vault position to improve and advance. In contrast, the deformation presence of a water-bearing hole causes the deformation of the vault position to increase and reach, while the deformation time of the arch foot position to delay.